UJI PENINGKATAN KADAR ASAM AMINO PADA TAPE KETAN HITAM DENGAN PENAMBAHAN SARI BUAH NANAS DENGAN METODE SPEKTROFOTOMETRI SINAR TAMPAK - Supartiningsih Supartiningsih; Siti Maimunah; Yosy Cinthya Eriwaty Silalahi (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Amino acid levels in sticky rice tape are still relatively low, while amino acids themselves are food substances for body growth. Pineapple contains the enzyme bromelain. This enzyme is one of the protease enzymes that can hydrolyze protein, therefore it can increase amino acid levels. This study aims to determine the increase in amino acid levels in black sticky rice tape with the addition of pineapple juice and to determine the effect of adding pineapple juice to amino acid levels in black sticky rice tape. In the process of making black sticky rice tape, 25 ml 50 ml of pineapple juice was added per 500 grams each, while one treatment did not add pineapple juice as a control. Black glutinous rice that has been fermented for 2-3 days was tested for increased levels of amino acids by using visible light spectrophotometry. The sample of black glutinous tape without the addition of pineapple juice obtained an average content of 4.73%, on the sample of black glutinous tape with the addition of 25 ml of pineapple juice the average content obtained was 6.50%, and the sample of black sticky rice tape with the addition of 50 ml pineapple juice the average level obtained was 7.76% and gave the effect of increasing amino acid levels on black sticky rice tape.